Sosialisasi Kepala Desa terkait Program Pengembangan Desa kepada Masyarakat Desa Batulayang - Enung Siti Halimatu Sadiah; Andalusia Neneng Permatasari (UNISBA Press, 2024)
Abstract. Implementing development in a village is a form of success for a village head. One of the efforts to make the development of religious programs in villages a success is to establish effective communication between the village head and the community. Community participation in maintaining and supporting programs taking place in Batulayang village. This is something that needs to be improved by the village head so that he can understand his community through various approaches. One of the most important approaches is to communicate and interact with them personally so that people feel cared for and recognized. Harmony in communication must always be maintained because it can affect people's mental attitudes. The aim of this research is to find out how the Village Head and the community communicate in Batulayang Village, Cililin subdistrict, the driving factors for communication between the Village Head and the community in Batulayang Village, Cililin subdistrict, as well as the community in the Batulayang Village religious program. This research uses qualitative methods and researchers use a case study approach. The results of the researchers were that the socialization carried out by the Batulayang Village Head was very effective in building community participation. The socialization process is carried out through various communication channels, both formal and informal, involving village staff, hamlet heads, RT/RW, as well as going directly to the community. The